2008
DOI: 10.1002/hep.22094
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of chronic hepatitis C in children: Liver biopsy findings in the Peds-C Trial

Abstract: There is relatively little information in the literature on the histopathology of chronic hepatitis C in children. The Peds-C Trial, designed to test the efficacy and safety of peginterferon alfa-2a and ribavirin in children, provided an opportunity to examine liver biopsies from 121 treatment-naïve children, ages 2 to 16 (mean, 9.8 years) infected with the hepatitis C virus (HCV) and with no other identifiable cause for liver disease, signs of hepatic decompensation, or another significant nonhepatic disease.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
139
3
13

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 173 publications
(162 citation statements)
references
References 29 publications
7
139
3
13
Order By: Relevance
“…However, if left untreated, chronic HCV infection can predispose pediatric patients to liver‐related complications, including cirrhosis and advanced liver disease 9, 10. Therefore, curative treatment of HCV infection should be considered for children and adolescents to mitigate the risk of liver disease progression, reduce the rates of transmission, and lessen the social stigma that can be associated with HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, if left untreated, chronic HCV infection can predispose pediatric patients to liver‐related complications, including cirrhosis and advanced liver disease 9, 10. Therefore, curative treatment of HCV infection should be considered for children and adolescents to mitigate the risk of liver disease progression, reduce the rates of transmission, and lessen the social stigma that can be associated with HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Decompensated cirrhosis in children as young as 4 years of age has been described 48, 78, 91, 92. HCV infection in children has also been suggested to negatively affect both health‐related quality of life and cognitive functioning; however, these findings would need to be confirmed in larger cohorts 93, 94…”
Section: Natural History Of Hcv Infection In Children and Adolescentsmentioning
confidence: 99%
“…Data were extracted from the seven studies 12,75,91,[93][94][95][96] identified and then pooled to give an estimate for the annual transition probability between mild HCV and moderate HCV, and moderate HCV and compensated cirrhosis. The transition probabilities used in the model for all other transitions were the same as for the previous NICE appraisals.…”
Section: Doi: 103310/hta18650mentioning
confidence: 99%